Ultraconserved elements are novel phylogenomic markers that resolve placental mammal phylogeny when combined with species-tree analysis - McCormack, John E.; Faircloth, Brant C.; Crawford, Nicholas G.; Gowaty, Patricia Adair; Brumfield, Robb T.; Glenn, Travis C. (Genome Research, 2012)
Phylogenomics offers the potential to fully resolve the Tree of Life, but increasing genomic coverage also reveals conflicting evolutionary histories among genes, demanding new analytical strategies for elucidating a single history of life. Here, we outline a phylogenomic approach using a novel class of phylogenetic markers derived from ultraconserved elements and flanking DNA. Using species-tree analysis that accounts for discord among hundreds of independent loci, we show that this class of marker is useful for recovering deep-level phylogeny in placental mammals. In broad outline, our phylogeny agrees with recent phylogenomic studies of mammals, including several formerly controversial relationships. Our results also inform two outstanding questions in placental mammal phylogeny involving rapid speciation, where species-tree methods are particularly needed. Contrary to most phylogenomic studies, our study supports a first-diverging placental mammal lineage that includes elephants and tenrecs (Afrotheria). The level of conflict among gene histories is consistent with this basal divergence occurring in or near a phylogenetic “anomaly zone” where a failure to account for coalescent stochasticity will mislead phylogenetic inference. Addressing a long-standing phylogenetic mystery, we find some support from a high genomic coverage data set for a traditional placement of bats (Chiroptera) sister to a clade containing Perissodactyla, Cetartiodactyla, and Carnivora, and not nested within the latter clade, as has been suggested recently, although other results were conflicting. One of the most remarkable findings of our study is that ultraconserved elements and their flanking DNA are a rich source of phylogenetic information with strong potential for application across Amniotes.